Organic agriculture as a factor influence on the level of nitrates in water from non-centralized sources of rural settlements - Romanchuk, L.; Valerko, R. (Scientific Progress & Innovations, 2024)
The article examines the impact of organic agriculture on nitrate levels in water from non-centralized water supply sources in rural areas of Ukraine. The intensive use of mineral fertilizers in conventional agriculture is identified as the primary cause of anthropogenic nitrate pollution in groundwater, posing a serious threat to public health. Organic agriculture, based on environmentally safe principles, is considered one of the approaches to reducing environmental pollution. The article characterizes the current state of organic farming development in Ukraine, highlighting the growth in the number of organic production operators. Attention is focused on the differences between organic and conventional farming approaches, as well as the potential of organic farming to reduce pollution of water resources. This study aimed to assess the impact of organic agriculture on nitrate levels in drinking water from non-centralized water supply sources in Ukrainian rural areas where both organic and conventional farming are practiced. Research was conducted in 14 Ukrainian regions, covering rural areas practicing organic and conventional agriculture, primarily focused on crop production. However, traditional farming methods have led to ecological imbalances, including soil degradation, water pollution, and reduced crop quality. The widespread use of nitrogen fertilizers in Ukraine has driven increased agricultural productivity, but plants absorb only about 50% of these fertilizers, with the remainder polluting the environment, including surface and groundwater. From 2016 to 2022, the application of organic fertilizers in Ukraine showed a gradual increase, driven by European integration processes promoting organic farming. Despite positive trends, the contribution of organic farming to water quality improvement is unclear. Research revealed that nitrate levels in non-centralized water sources frequently exceeded permissible levels, with variations between 50 % and 100 % across regions. Elevated nitrate concentrations were particularly prominent in areas practicing traditional farming. However, even in organic farming regions, some samples showed significant nitrate levels. The findings underscore the urgent need for policies promoting sustainable agricultural practices and enhanced monitoring of water quality. Expanding organic farming practices and integrating advanced farming techniques could mitigate nitrate pollution and improve environmental and public health outcomes. Further studies should explore the long-term effects of organic farming on groundwater quality to guide policy decisions.